Teaching Science in The New Normal: Understanding The Experiences of Junior High School Science Teachers - Arrieta, Gilbert Santos; Dancel, Jenalyn Cabana; Agbisit, Mark Jayson Pascua (Jurnal Pendidikan MIPA, 2020)
The Covid-19 pandemic has taken aback everyone that led to living unexpectedly in an environment called the new normal. One of the sectors seriously affected by this health crisis is education. With no face-to-face classes until a vaccine has been discovered, the Department of Education-Philippines (DepEd) believed that education should continue in school year 2020-2021 through online and other alternative modalities. The teachers in a private sectarian school in Manila began preparing as early as June 2020 leading to the creation of a learning continuity plan. One of the subjects in the junior high school seriously affected in doing online teaching and learning is Science. This study aims to explore and understand the experiences and challenges of the junior high school Science teachers after one term or almost three months of teaching in the new normal. The study found out that Science teachers were prepared and the curriculum was modified. Instructional materials were enhanced and various challenges were met like student discipline, delivery and execution of learning tasks, limited time for the implementation of the competencies, and student participation. Keywords: teaching science online, challenges of online teaching, science teachers creativity, initiatives and opportunities.  DOI: http://dx.doi.org/10.23960/jpmipa/v21i2.pp146-162